MORPHOLOGICAL ALTERATION OF CANINE NEUTROPHILS INDUCED WITH RECOMBINANT CANINE INTERLEUKIN-8 - Yasunobu Matsumoto; Yoshitsugu Matsumoto; Takashi Onodera; Satoshi Yamagoe; Kazuo Suzuki; Yoshikazu Hirota (Journal of Toxicologic Pathology, 1995)
Interleukin-8 (IL-8) is involved in the pathogenesis of a number of inflammatory diseases, such as rheumatoid arthritis, uveitis, pancreatitis, and ulcerative colitis. Molecular cloning of canine IL-8 was performed to establish a basis for its investigation in the canine immune system. Using an LPS-stimulated canine lymph node cDNA library as a temperate, we performed PCR amplification for the isolation of canine IL-8 CDNA. The 400-bp band amplified with the primers, was extracted from the gel and cloned into a pUC1I8 plasmid vector. The nucleotide sequences were determined. Escherichia coli DH5α strain was used for the transformation and production of fusion protein containing glutathione-S-transferase (GST) and canine IL-8. Produced GST-canine IL-8 fusion protein was treated with Factor Xa and recombinant canine IL-8 was purified. Neutrophil shape change assay showed strong biological activity of purified recombinant canine IL-8. In order to clarify the pathophysiological role of IL-8, it is necessary to have an ELISA systems for the quantitation of IL-8 in order to increase the specificity and sensitivity for the evaluation of canine IL-8.